RESILENSI MANTAN PECANDU NARKOBA PADA BADAN USAHA QUARRY UD. JASA SAHABAT SEBAGAI SARANA REHABILITASI DI KECAMATAN TAMPAN KOTA PEKANBARU - Hardiansyah, M. Haris; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Drug addictioan is a disease that can be cured with a stro effort and will for victims of abusers and effort to minimize the dependence on using drugs are rehabilitation efforts. And the persons who does it is called resilent. Resilence for drugs abusers requires a system to regulate how a drug addict can recover from addiction trought programs that are carried out in order to prevent abusers from relapse. The purpose of this study was to determin the role of UD. Jasa Sahabatas in instation that becomes a place for subjects to undrgo rehabilitation as a resilence. This research method of fenomenologi type with observation and interviews. The results is by working at Quarry UD. Jasa Sahabat, they are more able to minimize the dependence of using drugs to stop completely from being addicted to using drugs with a variety of motivasions and goals.Keywords : Resilence of Former Drug Addicts Who Make UD. Jasa Sahabat Serviece As a Means of Rehabilitation